2019
DOI: 10.1080/02770903.2019.1590590
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin treatment in children hospitalized with asthma: a retrospective cohort study

Abstract: Objective: Azithromycin has anti-inflammatory properties in the lungs and decreases the duration of asthma-like episodes in children. We sought to evaluate length of stay (LOS) and readmission rates of children receiving azithromycin therapy during hospitalization for acute asthma exacerbations. Methods: This was a retrospective cohort study at an urban, quaternary-care children's hospital including patients under 18 years old hospitalized for asthma, without concurrent infection, from 2002 to 2011. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…13,16 Recently, a retrospective observational study in approximately 20,000 adults with asthma exacerbation found that antibiotic therapy could be related to longer hospital stay, higher hospital cost, and similar risks of treatment failure. 1 Correspondingly, similar findings were observed from a retrospective observational study with approximately 5000 children hospitalized for asthma exacerbation 34 ; however, these findings were limited by the small sample size of the antibiotic therapy group (n 5 174) and the use of only 1 type of antibiotic (azithromycin). Our results extend the previous findings and confirm the lack of benefits of early treatment with antibiotics, including macrolide, cephalosporin, and penicillin, when added to systemic corticosteroids and short-acting b 2 -agonist inhalation among children hospitalized for asthma exacerbation in the absence of evidence of bacterial infection.…”
Section: Discussionsupporting
confidence: 59%
“…13,16 Recently, a retrospective observational study in approximately 20,000 adults with asthma exacerbation found that antibiotic therapy could be related to longer hospital stay, higher hospital cost, and similar risks of treatment failure. 1 Correspondingly, similar findings were observed from a retrospective observational study with approximately 5000 children hospitalized for asthma exacerbation 34 ; however, these findings were limited by the small sample size of the antibiotic therapy group (n 5 174) and the use of only 1 type of antibiotic (azithromycin). Our results extend the previous findings and confirm the lack of benefits of early treatment with antibiotics, including macrolide, cephalosporin, and penicillin, when added to systemic corticosteroids and short-acting b 2 -agonist inhalation among children hospitalized for asthma exacerbation in the absence of evidence of bacterial infection.…”
Section: Discussionsupporting
confidence: 59%
“…The results showed that clarithromycin therapy reduced mucosal TNF-α, IL-1β, and IL-10 concentrations in children with acute exacerbation of asthma [19]. In the third study, Johnston et al [6] reported that telithromycin treatment significantly improved the lung function, including the forced expira- tory volume in 1 s, resulting in a 50% reduction in asthma symptoms, in contrast to azithromycin, which induced no significant therapeutic benefit [20,21]. No study has yet reported that antibiotics can induce longer duration asthmatic symptoms, such as wheezing, in contrast to the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Despite experimental evidence, it has not yet been shown, that treatment with azithromycin as anti-viral and immunomodulatory agent has a significant impact on symptome scores, lung function parameters or length of stay during asthma exacerbations. 7 13 21 . Especially the high use in preschool age in our cohort should be critically discussed.…”
Section: Discussionmentioning
confidence: 99%